The effect of propofol when injected at different speeds for induction of general anesthesia: an observational study - Rather, Zahid Mohd; Rather, Mohd Nazrull islam; Afaq, Barqul; Farooq, Umar; Ara Majid, Nighat (International Journal of Clinical Trials, 2018)
Background: The hypotensive effect of propofol is attributable to a decrease in sympathetic activity, direct vasodilatation and myocardial depression. The aim of the study was to assess the effect of propofol when injected at different speeds for induction of general anesthesia on the following parameters: blood pressure, time of induction of anesthesia, dose of propofol used. Methods: The present study was conducted in post Graduate Department of Anesthesia and Surgery, Govt. Medical College, Srinagar for a period of two years and included 90 patients from July 2014 to June 16, the study was prospective one. Results: In our study patients divided into three groups with 30 patients in each group. The mean age in group P400, P600, P800 was statistically insignificant p>0.843.The mean weight in group P400, P600, P800 was statistically insignificant p>0.885.The mean height in group P400, P600, P800 was statistically insignificant p>0.748. The mean induction time in P400 and in P600 was statistically significant. The mean systolic blood pressure, pre and post induction in P400, in P600 and in group P800 was statistically significant. The mean diastolic blood pressure, in pre and post induction in P400, P600, P800 was statistically insignificant with a p>0.05. The mean arterial pressure in pre and post induction in P400, P600, P800 was statistically significant (p<0.05). The mean heart rate in pre and post induction was statistically insignificant. The mean oxygen saturation (%) pre and post induction was statistically insignificant. Conclusions: We concluded that induction dose required for loss of consciousness increased with a faster rate of infusion while time for induction was shorter in P800 compared to P400 and P600, and the decrease in mean blood pressure was less after induction in P400. Propofol injection should be slow enough to prevent any hemodynamic deterioration in anesthesia induction.